Amelioratory Effect of Nanoconjugated Vancomycin on Spleen during VRSA-Induced Oxidative Stress. (20th July 2011) - Chakraborty, Subhankari Prasad; KarMahapatra, Santanu; Sahu, Sumanta Kumar; Pramanik, Panchanan; Roy, Somenath
Abstract : Objective . The aim of the present study was to evaluate the possible antioxidant effects of nanoconjugated vancomycin against VRSA infection on select makers of oxidative damage and antioxidant status in spleen. Methods . A coagulase-positive VRSA strain was used for this study. VRSA infection was developed in Swiss mice by intraperitoneal injection of 5 × 10 6  CFU/mL bacterial solutions. VRSA-infected mice were treated with nanoconjugated vancomycin at its effective dose for 10 days. After decapitation, blood was used for determination of viable bacteria count and spleen was excised from control and experimental groups, homogenized and used for different biochemical estimations. Results . Nitrate level, myeloperoxidase activity, lipid peroxidation, protein oxidation, oxidized glutathione, and DNA fragmentation level were increased significantly (P < 0.05 ) in spleen of VRSA-infected group as compared to control group, and reduced glutathione level, activity of SOD, CAT, GPx, GR, and GST were decreased significantly (P < 0.05 ); which were increased or decreased significantly (P < 0.05 ) near to normal in nanoconjugated vancomycin-treated group. Conclusion . These findings suggest the potential use and beneficial role of nanoconjugated vancomycin against VRSA-infection-induced oxidative stress and DNA damage in spleen.